Artificial Human Optimization – An Overview - Gajawada, Satish; M. H. Mustafa, Hassan (Transactions on Engineering and Computing Sciences, 2018)
The main idea to author this article is to “Popularize Artificial Human Optimization Field like never before by showing an Overview of this new field”. This idea can be divided into following sub-ideas: 1) To show the definition of “Artificial Human Optimization Field (AHO Field)” 2) To show difficulty level of creating new algorithms under AHO field 3) To show 30+ titles of papers published under AHO field 4) To show names of 65+ authors who worked under AHO Field 5) To show best negative reviews obtained for work under AHO Field 6) To show best positive reviews obtained for work under AHO Field 7) To show feedback given by an expert for work under AHO Field 8) To show “Hassan Satish Particle Swarm Optimization (HSPSO)”. This is latest work under AHO Field 9) To show contribution of Satish Gajawada and co-authors to this new Field 10) To show surprising results obtained after implementing AHO algorithms 11) To show you “Future of Artificial Human Optimization Field”